Effects of hemicellulose on intestinal mucosal barrier integrity, gut microbiota, and metabolomics in a mouse model of type 2 diabetes mellitus - Liu, Huan; Xu, Jihao; Yeung, Chiuwing; Chen, Qikui; Li, Jieyao (Frontiers in Microbiology, 2023)
Background and objective Impaired gut barrier contributes to the progression of type 2 diabetes mellitus (T2DM), and the gut microbiota and metabolome play an important role in it. Hemicellulose, a potential prebiotics, how its supplementation impacted the glucose level, the impaired gut barrier, and the gut microbiota and metabolome in T2DM remained unclear. Methods In this study, some mice were arranged randomly into four groups: db/db mice fed by a compositionally defined diet (CDD), db/db mice fed by a CDD with 10% and 20% hemicellulose supplementation, and control mice fed by a CDD. Body weight and fasting blood glucose levels were monitored weekly. The gut barrier was evaluated. Fresh stool samples were analyzed using metagenomic sequencing and liquid chromatography-mass spectrometry to detect gut microbiota and metabolome changes. Systemic and colonic inflammation were evaluated. Results Better glycemic control, restoration of the impaired gut barrier, and lowered systemic inflammation levels were observed in db/db mice with the supplementation of 10 or 20% hemicellulose. The gut microbiota showed significant differences in beta diversity among the four groups. Fifteen genera with differential relative abundances and 59 significantly different metabolites were found. In the db/db group, hemicellulose eliminated the redundant Faecalibaculum and Enterorhabdus. The increased succinate and ursodeoxycholic acid (UDCA) after hemicellulose treatment were negatively correlated with Bifidobacterium, Erysipelatoclostridium, and Faecalibaculum. In addition, hemicellulose reduced the colonic expressions of TLR2/4 and TNF-α in db/db mice. Conclusion Hemicellulose may serve as a potential therapeutic intervention for T2DM by improving impaired intestinal mucosal barrier integrity, modulating gut microbiota composition, and altering the metabolic profile.